Designing introvert-friendly public spaces in Malaysia - Wee, Branda; Mohd Noor, Mohd Zairul; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
Public spaces are often designed with extroverted behaviours in mind, overlooking the needs of introverted individuals who prefer quieter, less stimulating environments. In Malaysia, this oversight results in public spaces that fail to cater to introverts, causing discomfort and diminished well-being. Despite this, there is a noticeable lack of research and practical guidelines for creating introvert-friendly public spaces in the Malaysian context. This study aims to address this gap by developing effective design strategies tailored for introverts. The research will identify key spatial features and design elements that promote introvert-friendly environments and propose practical guidelines for their implementation. The findings will raise awareness among architects and urban planners, leading to public spaces that better support introverts' needs, thereby enhancing their comfort and well-being.